Content validity of the EQ-HWB and EQ-HWB-S in a sample of Italian patients, informal caregivers and members of the general public - Sara Masutti; Camilla Falivena; Fredrick Dermawan Purba; Claudio Jommi; Clara Mukuria; Aureliano Paolo Finch (SpringerOpen, 2024)
Abstract Background The EuroQol Group recently developed two new instruments, the EQ Health and Wellbeing (EQ-HWB) and the EQ Health and Wellbeing short version (EQ-HWB-S). The EQ-HWB and EQ-HWB-S are intended to capture a broad range of health and broader quality of life aspects, which may be relevant to general public members, patients, their families, social care users and informal carers. This study assesses the content validity of the Italian version of the two instruments in a sample of Italian patients, social care users and informal carers. Methods Participants were recruited using a convenience sampling approach. One-on-one interviews were carried out using video-conferencing interviews. A semi-structured topic guide was used to guide the interview procedures, with open-ended questions supplemented by probes. Participants were asked to explain important aspects of their health and quality of life, to complete the questionnaires and verbalize their thoughts. Results Twenty participants comprising of patients (n = 9), informal carers (n = 6), and members of the general public (n = 5) participated to the study. Content validity was summarized into six main themes: comprehension, interpretation, acceptability, relevance, response options and recall period. All participants found the instruments easy or quite easy to understand and to respond to. Items were relevant for all three groups of participants, and response options appropriate. Conclusions The Italian version of the EQ-HWB showed content validity in measuring health and wellbeing in a mixed Italian population.